Pengembangan LKPD Menulis Teks Pidato Berbasis Inkuiri Terbimbing Siswa Kelas IX SMP - Candra Pratiwi; Sumarti Sumarti; Nurlaksana Eko Rusminto (Universitas Lampung, 2019)
The purpose of this research was to produce teaching material, to describe the appropriateness of the teaching material, and to test the effectiveness of the teaching materials in the from of LKPD writing speech text based on guided inquiry for the student on the third grade (on the IX’s class) in Junior High School. This research used research and development with three adapted phases. The data were obtained through observation, interview, and spreading the quiestionaire at the three Junior High School. The results of the research showed that 1) the teaching materials in the form of “LKPD Writing Speech Based on Guided Inquiry for The Student on the IX’s class in Junior High School was successfully developed, 2) overall, the student activities sheet was claimed “very appropriate” by the teaching material development experts, media experts, and practioners with a percentage rating 93,96, 90,51 and 90,78, and 3) the student activity sheets effectivelly improved the student writing ability to write speech text. The N-gain value of 0,81, 0,699, and 0,67 included in medium category.Penelitian bertujuan menghasilkan produk bahan ajar, mendeskripsikan kelayakan produk bahan ajar, dan menguji efektivitas bahan ajar berupa “LKPD Menulis Teks Pidato Berbasis Inkuiri Terbimbing untuk Siswa Kelas IX SMP”. Metode penelitian menggunakan desain penelitian dan pengembangan yang diadaptasi menjadi tiga tahapan utama. Teknis pengumpulan data dengan observasi, wawancara, dan penyebaran angket di tiga sekolah. Hasil penelitian 1) berhasil dikembangkan bahan ajar berupa “LKPD Menulis Teks Pidato Berbasis Inkuiri Terbimbing”, 2) kelayakan lembar kegiatan peserta didik secara keseluruhan dinyatakan “sangat layak” oleh ahli materi, ahli media, dan praktisi dengan persentase penilaian 93,96, 90,51, dan 90,78, 3) lembar kegiatan peserta didik efektif meningkatkan kemampuan menulis narasi pada masing-masing sekolah dengan nilai N-gain sebesar (0,81), (0,69), dan (0,67) termasuk dalam kategori sedang.Kata kunci: inkuiri terbimbing , lkpd, pidato.